Impact of laser therapy on the condition of oral cavity mucosa in chemotherapy treated patients who underwent bone marrow transplantation - Bąk, Tomasz Krzysztof; Schab, Katarzyna Ewa; Topyła, Weronika Sandra; Ziomek, Jaromir Paweł; Wojciechowicz, Jolanta Elżbieta; Tomaszewski, Tomasz (Journal of Education, Health and Sport, 2017)
Patological disorders within oral mucosa (so called mucositis) are the most common stomatological complications among chemotherapy treated leukemic patients scheduled for bone marrow transplantation. Early diagnosis of such oral disorders leads to numerous side effects, decreasing quality of life and systemic complications is required. Furthermore, most patients require analgesic treatment, very often using narcotic pain medications. Presently the largest role of prevention and treatment of mucositis is preventative dentistry along with maintaining strict oral hygiene. This course of action aims to reduce pain and prevention of infections. Investigation of novel non-invasive therapeutic methods that could improve treatment outcomes seems justified. Among the most promising methods, the Low-level Laser Therapy (LLLT) treatment demonstrates many beneficial effects for patients suffering from chemotherapy complications. It promotes mucosal healing and helps improve patients’ quality of life. These advantages may be a result of a LLLT anti-inflammatory and analgesic effect. LLLT also promotes tissue regeneration through chemical changes in cells (cell repair). In recent clinical studies conducted on a group of patients with oral mucositis, the significant acceleration of mentioned disorders regression was noted. Moreover, reduction of pain after application of LLLT was recorded. Discussed in the article LLLT is easily accessible for clinical practice . Mentioned arguments justify a wider use of such a tool in non-invasive treatment of acute oral cavity inflammation.